INNOVATIVE METHODS OF TEACHING ENGLISH LANGUAGE - Sayfullayeva Umida Ulmaskulovna (Research Focus International Scientific Journal, 2025)
As methodological and psychological-pedagogical studies show, the use of role-playing communicative games opens up wide opportunities for activating and optimizing the educational process, which is an important means of organizing pair and group work. The motivation for mastering a foreign language, first of all, is the professional need of a student who is preparing to become a highly qualified specialist with knowledge of a foreign language.